Making Instant Adjustments in Online Journalism Education: Responding to Continuous Needs Assessments in Asynchronous Courses - Bright, Amanda C. (Online Learning, 2020)
The creation of an ideal learning environment is always a challenge, but when the environment is online and the learners are a diverse group of adults in a specialized content area, the challenges become even more complex. This best practices study used the intersection of the importance of the learner, Knowles’ andragogy concepts, and the Dick and Carey instructional design model to make continuous needs assessment the cornerstone of three, graduate-level online courses during a single summer session. By active engagement in recursive learner analysis, the instructor was able to provide a personal and practical level of engagement in the asynchronous courses that ultimately benefited the students.